Role of odanacatib in reducing bone loss due to endodontic disease: An overview - Bahuguna, Rachana (J Int Soc Prev Community Dent, 2016)
AIMS AND OBJECTIVES: Through a comprehensive literature review, this article provides an overview of the potential role of odanacatib (ODN) in reducing bone loss due to endodontic disease. MATERIALS AND METHODS: A literature review was performed in PubMed Central, MEDLINE, Cochrane Library, and EBSCO databases. The articles identified included those published between 2002 and 2016. Based on the predetermined inclusion and exclusion criteria, out of 237 articles found, 50 were selected for this review. RESULTS: Cathepsin K (CstK), which is indispensible to the immune system, also plays an important role in osteoclastic bone resorption. ODN, which is an orally active, selective, and effective inhibitor of CstK, decreases bone resorption by selectively inhibiting proteolysis of matrix proteins by CstK, without affecting other osteoclastic activity or osteoblast viability. CONCLUSION: The goal of endodontic treatment is to achieve a clinically asymptomatic state along with formation of reparative bone. This process could take 6 months or longer, hence, an earlier reversal of the resorption process could lead to faster healing and resolution of the periapical lesion. Use of ODN can be of help in achieving this goal.